Status or fun? A cross-cultural examination of young consumers' responses to images of champagne and sparkling wine. Issue 8 (1st August 2016) - Velikova, Natalia; Charters, Steve; Fountain, Joanna; Ritchie, Caroline; Fish, Nicola; Dodd, Tim
Abstract : Purpose: – The purpose of this paper is to test Luna and Gupta's (2001) investigative framework on the interaction of cultural values and consumer behaviour by conducting a cross-cultural comparison of young wine consumers' interpretation of images of champagne and sparkling wine. The research examined consumer responses to the images through the prism of the relationship between symbolism, ritual and myth, as well as other related values. Design/methodology/approach: – In a series of focus groups with consumers from four anglophone countries (the USA, New Zealand, Australia and the UK), six images of champagne and sparkling wine were used as stimuli to encourage affective and cognitive perspectives on the topic. Findings: – Overall, the UK market showed distinct differences from the other markets, due very much to its cultural context. The UK consumers valued traditional advertising; focused mainly on the product itself; and did not associate champagne with fun. Respondents from the New World focused on the general impression of the image and on enjoyment and fun associated with consumption of champagne and sparkling wine. Practical implications: – The most crucial implication of this research is the cultural variation in consumer perceptions of champagne and sparkling wine and the impact that it has upon marketing strategies on how to market this product category to younger consumers in different markets. Originality/value: – This research contributes to the study of cultural values and consumption behaviour, as well as image effectiveness in forming perceptions of the product category.